2020
DOI: 10.1016/j.neucom.2019.12.069
|View full text |Cite
|
Sign up to set email alerts
|

Echo state network optimization using binary grey wolf algorithm

Abstract: The echo state network (ESN) is a powerful recurrent neural network for time series modelling. ESN inherits the simplified structure and relatively straightforward training process of conventional neural networks, and shows strong computational capabilities to solve nonlinear problems. It is able to map low-dimensional input signals to high-dimensional space for information extraction, but it is found that not every dimension of the reservoir output directly contributes to the model generalization. This work a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The outcomes reveal that the new GWO scheme outperforms the detection methods mentioned in the literature in most cases. Liu et al [65] developed a new artificial neural network and deep learning model, the binary grey wolf echo state network. The performance of the developed hybrid model was analyzed using different datasets.…”
Section: Performance Evaluation Of Modelsmentioning
confidence: 99%
“…The outcomes reveal that the new GWO scheme outperforms the detection methods mentioned in the literature in most cases. Liu et al [65] developed a new artificial neural network and deep learning model, the binary grey wolf echo state network. The performance of the developed hybrid model was analyzed using different datasets.…”
Section: Performance Evaluation Of Modelsmentioning
confidence: 99%
“…ESN simplifies the training task of the network, in which only the weights of the output matrix should be trained without the traditional backpropagation. e topology structure of ESN is shown in Figure 1 [33].…”
Section: Echo State Networkmentioning
confidence: 99%
“…In the second approach, a sigmoid function is used to squash the continuous updated position, then stochastically threshold these values to find the updated binary gray wolf position. In the next years, their work was adapted by many others such as (Liu et al, 2020) and (Devanathan et al, 2019). Manikandan et al suggested new binary modifications of GWO for choosing optimal elements subsets (Manikandan et al, 2016).…”
Section: Related Work On Binarization Of Gwomentioning
confidence: 99%